BIOMECHANICAL CHARACTERISTICS OF THROWING TECHNIQUES IN COMPARATIVE ANALYSIS WITH OLYMPIC WRESTLING STYLES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The purpose of the article: to systematize the biomechanical characteristics of throwing techniques in Qazaq kuresi and compare them with the requirements and movement patterns of Olympic wrestling (Greco-Roman and freestyle). The analysis was based on the UWW rules for Qazaq kuresi and Olympic wrestling, as well as scientific sources on the biomechanics of throws in wrestling and related sports (judo). It is shown that in Qazaq The evaluation criteria directly capture the "biomechanical quality" of the throw (speed, amplitude, phase completion, post-throw control), which emphasizes the role of explosive extension of the lower extremities, rotational moments in the pelvic -lumbar complex, and control of the opponent's center of mass. In Greco-Roman wrestling, the restriction on attacks below the waist shifts the load to the core and upper shoulder girdle; in freestyle wrestling, the ability to attack with legs increases the proportion of maneuvers involving changes in level and combined support. A set of measurable biomechanical indicators (kinematics, kinetics, phase timing) and a comparative table of expected differences are proposed.